2010
DOI: 10.4161/chan.4.4.12130
|View full text |Cite
|
Sign up to set email alerts
|

CaV2.1 (P/Q channel) interaction with synaptic proteins is essential for depolarization-evoked release

Abstract: It is well-established that syntaxin 1A (Sx1A), SNAP-25 and synaptotagmin (Syt1) either alone or in combination, modify the kinetic properties of voltage-gated Ca(2+) channels (VGCCs). The interaction interface resides mainly at the cytosolic II-III domain of the alpha1 subunit of the channels, while Sx1A interacts with the channel also via two highly conserved cysteine residues at the transmembrane domain. In the present study, we characterized Ca(2+)-independent coupling of the human neuronal P/Q-type calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 66 publications
4
24
0
Order By: Relevance
“…Finally, introducing point mutations in the TS channel that prevent Ca 2+ flux through the channel does not prevent the channel from triggering retraction. These results are consistent with the idea that Ca V 1.2 channels can activate signaling cascades by voltage-dependent conformational changes 48,49 , reminiscent of the physical mechanism by which a related channel Ca V 1.1 causes excitation-contraction coupling in skeletal muscle 50 .…”
Section: Discussionsupporting
confidence: 90%
“…Finally, introducing point mutations in the TS channel that prevent Ca 2+ flux through the channel does not prevent the channel from triggering retraction. These results are consistent with the idea that Ca V 1.2 channels can activate signaling cascades by voltage-dependent conformational changes 48,49 , reminiscent of the physical mechanism by which a related channel Ca V 1.1 causes excitation-contraction coupling in skeletal muscle 50 .…”
Section: Discussionsupporting
confidence: 90%
“…9 SNAP25 is a part of a multiprotein complex implicated in the regulation of channel activity through modulation of the transport and membrane localization of the channel and inhibition of channel activation. 10,11 In particular, SNAP25 is thought to modulate the kinetics of voltage-gated Ca(21) channels, including the Ca v 2.1 calcium channel linked to HM.…”
Section: Discussionmentioning
confidence: 99%
“…Results of a yeast two-hybrid assay indicated that PRRT2 and SNAP25 interact 62,63. SNAP25 affects neurotransmitter release from the synapse and can regulate calcium channel dynamics, including for the Cav2.1 calcium channel 64. Some investigators have hypothesized that PRRT2 mutation impairs SNAP25 function, which then changes CaV2.1 activity, causes neuronal hyperexcitability, and results in epilepsy, hemiplegic migraine, or PKD.…”
Section: Prrt2 Genementioning
confidence: 99%